Metallic light-based bird-repellent prototype to reduce paddy yield loss in Jatinangor, Sumedang Regency - Santriyani, Ai Siti; Bari, Ichsan Nurul; Natawigena, Wahyu Daradjat; Puspasari, Lindung Tri; Subakti-Putri, Syifa Nabilah (Kultivasi, 2024)
Munia birds (Lonchura spp.) are pests that attack paddy plants during the reproductive phase. The traditional methods of controlling birds are considered less effective because birds can adapt to the tools used. This study aimed to determine the effectiveness of a metallic light-based bird-repellent prototype to reduce paddy yield loss. The experiment was conducted in Cileles Village paddy fields, Jatinangor Subdistrict, Sumedang Regency, West Java Province, Indonesia. The effectivity of the prototype was tested by measuring the effective distance (m2), counting the frequency of bird visits (number of visits), bird populations, and the level of paddy damage (%), and paddy yield (kg/64 m2). The result of the experiment showed that 3 m was an effectual deterrent factor for the prototype, thus the tool can protect paddy plants with an area of 28.26 m2. The frequency of bird arrivals in the treatment was 22.25 times, compared to 61.25 times in the control; the bird population in the treatment was 48.25 birds, while the control was 108.75 birds; the level of damage to paddy panicles in the treatment was 10.11%, compared to 37.79% in the control; and the production of paddy yield with the repellent was higher (33.37 kg/64 m2) than the control (23.09 kg/64 m2). This innovative prototype was potentially able to deter bird pests in the paddy fields.